2015
DOI: 10.1002/cctc.201500139
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light‐Induced CC Bond Cleavage of Enaminones for the Synthesis of 1,2‐Diketones and Quinoxalines in Sustainable Medium

Abstract: The CC double bond cleavage of enaminones has been realized under ambient conditions through visible‐light catalysis in the presence of Rose Bengal, which leads to the synthesis of a class of 1,2‐diketones without using any metal catalyst. In addition, the one‐pot synthesis of quinoxalines has also been achieved under identical photocatalytic conditions by making use of the in situ generated 1,2‐diketones as intermediates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(20 citation statements)
references
References 90 publications
1
19
0
Order By: Relevance
“…In recent years, ethyl lactate (EL) has been introduced as a possible environmentally safe solvent in organic synthesis due its intrinsic characteristics such as low price, less toxicity, good biodegradability, high stability as well as solubility to both water and organic compounds . Literature survey shows that EL has been used in some organic transformations such as coupling reactions, cycloaddtion reaction, multi‐component reactions, light induced synthesis, and stereoselective synthesis . Therefore, it is worth emphasizing that the development of an efficient and rapid synthetic route for the preparation of biologically and drug active molecules by combining the synthetic efficiency of ultrasonic‐assisted organic reactions and advantages of EL as reaction medium under catalyst free conditions is highly desirable and deserves significant attention.…”
Section: Optimization Of Reaction Condition[a]mentioning
confidence: 99%
“…In recent years, ethyl lactate (EL) has been introduced as a possible environmentally safe solvent in organic synthesis due its intrinsic characteristics such as low price, less toxicity, good biodegradability, high stability as well as solubility to both water and organic compounds . Literature survey shows that EL has been used in some organic transformations such as coupling reactions, cycloaddtion reaction, multi‐component reactions, light induced synthesis, and stereoselective synthesis . Therefore, it is worth emphasizing that the development of an efficient and rapid synthetic route for the preparation of biologically and drug active molecules by combining the synthetic efficiency of ultrasonic‐assisted organic reactions and advantages of EL as reaction medium under catalyst free conditions is highly desirable and deserves significant attention.…”
Section: Optimization Of Reaction Condition[a]mentioning
confidence: 99%
“…During the continuous exploration, the metal‐free, photocatalytic carbonylation of tertiary enaminones was realized by using rose bengal (RB) as the photocatalyst 35. It was found that irradiation with a 15 W LED bulb could efficiently induce the C=C double bond cleavage of enaminones 55 to yield various vicinal diketones 56 at room temperature.…”
Section: Reactions Based On the C=c Double Bond Cleavagementioning
confidence: 99%
“…In addition, direct employment of o ‐phenylenediamines 24 in this visible‐light catalytic system enabled the one‐pot synthesis of quinoxalines 23 . The oxidation reactions were carried out in air and were proposed to be initiated by the formation of peroxide intermediate 25 through the oxidation of singlet oxygen (Scheme ) …”
Section: Carbonyl Formation Through Oxygenation Based On Full Cleavamentioning
confidence: 99%